2012
DOI: 10.2174/187153012800493521
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Effects of HDL and Its Components on Diabetic Cardiomyopathy

Abstract: Diabetic cardiopathy includes a specific cardiomyopathy, which occurs in the absence of coronary heart disease and hypertension under diabetes mellitus. Hyperglycemia, hyperinsulinemia, and hyperlipidemia, characteristic metabolic disturbances evident in diabetes mellitus, all three lead to a specific altered cardiac structure and function. Recently, it has been demonstrated that altered HDL, be it low HDL or dysfunctional HDL is not only a consequence of diabetes mellitus, but can also contribute to the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 170 publications
(205 reference statements)
0
10
0
Order By: Relevance
“…The main cellular mechanisms that are commonly involved in cardiac remodeling and function during DCM progression are depicted in Figure 3 [19]. These are thought to mainly be triggered by the metabolic consequences of dysfunctional insulin signaling [72], which leads to a series of events that results in cardiac lipotoxicity (Section 2). Lipotoxicity can aggravate chronic cardiac and vascular dysfunction ( Figure 3) [7,19,70].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…The main cellular mechanisms that are commonly involved in cardiac remodeling and function during DCM progression are depicted in Figure 3 [19]. These are thought to mainly be triggered by the metabolic consequences of dysfunctional insulin signaling [72], which leads to a series of events that results in cardiac lipotoxicity (Section 2). Lipotoxicity can aggravate chronic cardiac and vascular dysfunction ( Figure 3) [7,19,70].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Decreased high-density lipoprotein (HDL) and apolipoprotein A-I (ApoA-l) levels in the general population are associated with an increased risk of mortality from ischemic cardiomyopathy and heart failure [ 20 , 21 ]. Cardiomyopathy and heart failure are also risk factors that are elevated in FA [ 6 8 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrated that inflammation and dyslipidaemia act synergistically in organ injuries 11, 12. Ruan and colleagues demonstrated that inflammatory stress exacerbated lipid accumulation via disruption of LDL receptor (LDLr) feedback regulation in the aorta, liver or kidney 13-15.…”
Section: Introductionmentioning
confidence: 99%